Single‐Nucleus RNA Sequencing Reveals that Decorin Expression in the Amygdala Regulates Perineuronal Nets Expression and Fear Conditioning Response after Traumatic Brain Injury. Issue 7 (17th January 2022) - Shi, Yingwu; Wu, Xun; Zhou, Jinpeng; Cui, Wenxing; Wang, Jin; Hu, Qing; Zhang, Shenghao; Han, Liying; Zhou, Meixuan; Luo, Jianing; Wang, Qiang; Liu, Haixiao; et al.
Abstract: Traumatic brain injury (TBI) is a risk factor for posttraumatic stress disorder (PTSD). Augmented fear is a defining characteristic of PTSD, and the amygdala is considered the main brain region to process fear. The mechanism by which the amygdala is involved in fear conditioning after TBI is still unclear. Using single‐nucleus RNA sequencing (snRNA‐seq), transcriptional changes in cells in the amygdala after TBI are investigated. In total, 72 328 nuclei are obtained from the sham and TBI groups. 7 cell types, and analysis of differentially expressed genes (DEGs) reveals widespread transcriptional changes in each cell type after TBI are identified. In in vivo experiments, it is demonstrated that Decorin (Dcn) expression in the excitatory neurons of the amygdala significantly increased after TBI, and Dcn knockout in the amygdala mitigates TBI‐associated fear conditioning. Of note, this effect is caused by a Dcn‐mediated decrease in the expression of perineuronal nets (PNNs), which affect the glutamate‐ γ ‐aminobutyric acid balance in the amygdala. Finally, the results suggest that Dcn functions by interacting with collagen VI α 3 (Col6a3). Consequently, the findings reveal transcriptional changes in different cell types of the amygdala after TBI and provide direct evidence that Dcn relieves fear conditioning by regulating PNNs. Abstract : Single‐nucleus RNA sequencing is employed to investigate the transcriptional changes of individual cells from the amygdala tissues of sham and traumatic brain injury (TBI) mice. Decorin is significantly increased in excitatory neurons. Decorin knockout in the amygdala could mitigate TBI‐induced fear condition. Of note, high Decorin expression suppresses the expression of perineuronal nets by interacting with collagen VI α 3.